2011
DOI: 10.1007/s00210-011-0614-1
|View full text |Cite
|
Sign up to set email alerts
|

Weight and inflammation are the major determinants of vascular dysfunction in the aortae of db/db mice

Abstract: The key roles that obesity, hyperglycemia, hyperlipidemia, inflammation, and oxidative stress play in the progression of diabetes vascular complications are well recognized; however, the relative contribution and importance of these individual factors remain uncertain. At 6, 10, or 14 weeks old, blood samples and thoracic aortae were collected from db/db mice and their non-diabetic controls. Plasma samples were analyzed for glucose, 8-isoprostane, CRP, triglycerides, LDL, and HDL as markers of glycemic status,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 88 publications
(106 reference statements)
2
17
0
Order By: Relevance
“…It has been previously demonstrated that CIH induces inflammation through increased levels of IL-6 [38, 39]. Inflammation that occurs in diabetes is an important contributor of vascular dysfunction in db/db mice [18, 40]. Our data demonstrates that the increased levels of IL-6 in db/db mice were not further exacerbated by CIH, likely due to the already high levels of inflammation already present in diabetic mice.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…It has been previously demonstrated that CIH induces inflammation through increased levels of IL-6 [38, 39]. Inflammation that occurs in diabetes is an important contributor of vascular dysfunction in db/db mice [18, 40]. Our data demonstrates that the increased levels of IL-6 in db/db mice were not further exacerbated by CIH, likely due to the already high levels of inflammation already present in diabetic mice.…”
Section: Discussionsupporting
confidence: 61%
“…Cleaned aortic blood vessels were cut into equal 2 mm rings and mounted on a wire myograph for measuring isometric tension (DMT 620M, Danish Myotechnology, Aarhus, Denmark) as described previously [18]. Each myograph chamber contained PSS kept at 37°C and pH 7.4 with constant administration of 95% O 2 and 5% CO 2 gases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The db gene encodes a G-to-T point mutation of the leptin receptor, which causes a defect affecting hypothalamic responses and leads to the development of hyperphagia, obesity, hyperlipidemia, hyperinsulinemia, insulin resistance, and diabetes [20], [21]. Our results suggest that chronic treatment of diabetic animals with resveratrol improves glucose tolerance, attenuates β-cell loss and reduces oxidative stress.…”
Section: Introductionmentioning
confidence: 64%
“…It causes the hyperpolarisation of the membranes of the fungal cells, which leads to the disintegration of the membranes and, consequently, an apoptosis-like phenotype appears. Furthermore, reactive oxygen species oxidize intracellular proteins, lipids, and nucleic acids, causing not only the disintegration of the cellular membranes but also that of the mitochondria (20). These toxic effects, when they reach a critical limit, also contribute to the programmed cell death of the affected fungi (6).…”
Section: Introductionmentioning
confidence: 99%